MICROFOSSILS FROM THE UPPER RIPHEAN TYPE SECTION (THE KARATAU GROUP OF SOUTHERN URALS) - Veis A.F.; Vorob'eva N.G.; Kozlov V.I.; Sergeeva N.D. (My University, 2003)
New materials studied (over 200 samples) and published data critically analyzed are used to specify composition of organic-walled microfossils and to elucidate their vertical and lateral distribution in the Upper Riphean type section, the Karatau Group of southern Urals that is divided into six formations. New burials of microfossils are discovered in the Zilmerdak, Inzer, Min'yar, and Uk formations. Microfossils most important in terms of stratigraphy are established in a basal interval of the group (Nugush and Bederysh subformations of the Zilmerdak Formation) and near the base of the Inzer Formation. According to results obtained, the microfossil assemblages from above subdivisions include some transit taxa formerly unknown and abundant morpho-types of a complex structure, which appear for the first time at these stratigraphic levels. The pre-Nugush, pre-Bederysh, and pre-Inzer levels are most significant among microphytological boundaries established in the Karatau succession of microfossils. The first of them is marked by the first occurrence of large acritarchs Chuaria and Navifusa in association with morphotypes of filamentous and other complex structures. The particular species of acanthomorphic Trachyhystrichosphaera and associated Arctacellularia, Tortunema, and Glomovertella forms are characteristic of the second level, whereas the third one signifies appearance of Prolatoforma, Tasmanites, Pellicularia, Eosaccharomyces, and some other taxa. The comparative analysis of South Uralian and other regional successions of microfossils implies that the microbiotas are applicable for biostratigraphic subdivision of the Upper Riphean.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей